2013
DOI: 10.1021/es401555x
|View full text |Cite
|
Sign up to set email alerts
|

Forward Osmosis with a Novel Thin-Film Inorganic Membrane

Abstract: Forward osmosis (FO) represents a new promising membrane technology for liquid separation driven by the osmotic pressure of aqueous solution. Organic polymeric FO membranes are subject to severe internal concentration polarization due to asymmetric membrane structure, and low stability due to inherent chemical composition. To address these limitations, this study focuses on the development of a new kind of thin-film inorganic (TFI) membrane made of microporous silica xerogels immobilized onto a stainless steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Studies conducted recently have focused on hydrophilic magnetic nanoparticles (MNPs) [118]. Three different types of MNPs have been investigated as potential draw solution for FO desalination.…”
Section: Magnetic Nanoparticles Draw Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted recently have focused on hydrophilic magnetic nanoparticles (MNPs) [118]. Three different types of MNPs have been investigated as potential draw solution for FO desalination.…”
Section: Magnetic Nanoparticles Draw Solutionmentioning
confidence: 99%
“…Tang et al have modeled a similar double-skinned FO membrane and have observed that the best double-skinned FO membrane should maintain a mass transfer coefficient that is high for the porous support, have a brackish water RO type draw skin, a feed skin with low rejection NF [142]. Su et al have also fabricated double-skinned CA hollow fibers consisting of an inner or outer selective layer by employing different phase inversion rates and extent of thermal annealing at Electro-spinning, phase separation and IP [135] 2012 TFC PA Super porous CNT non-woven Bucky-paper (BP) support, PA active layer Plasma treatment of CNT BPs support and IP [136] 2012 Dual layer hollow fiber NF PES inner support layer and PAI active layer post-treated by PEI Dry-jet wet spinning, one-step coextrusion, multi-layer polyelectrolyte depositions [137] 2013 Thin-film inorganic (TFI) Stainless steel mesh (SSM) substrate, micro-porous silica xerogels active layer Dip-coating and calcining for 4 h at 500°C in nitrogen followed by cooling to 25°C [118] 2014 Thin-film nanocomposite (TFN)…”
Section: Membrane Advancementmentioning
confidence: 99%
“…Novel membranes, based on materials ranging from carbon nanotubes to graphene to aquaporin proteins, could potentially achieve greater water permeabilities and solute rejections, and are the subject of active research [22][23][24][25][26]. Innovative fabrication techniques are also being investigated in attempts to further lower the mass transport resistance of FO membrane support layers and enhance productivity [20,[27][28][29][30][31]. 3 Previous studies have investigated the trade-off between water and solute permeability of the membrane active layer [32,33] and the effect of morphology and microstructure on concentration polarization within the membrane support layer [28,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…LbL assembly has also been used to fabricate thin-film inorganic (TFI) membrane [165]. This membrane was prepared by layer-bylayer deposition of silica xerogels onto the stainless steel mesh (SSM) substrate.…”
Section: Chemically Modified Fo Membranesmentioning
confidence: 99%